Pengaruh Remunerasi, Lingkungan Kerja dan Kompetensi Terhadap Kepuasan Kerja - Aysyah Rengganis; Ade Yovi Novalesi; Ishak Hanawi; Muhammad Nasir; Hasrita Lubis; Ismail Nasution (Journal of Trends Economics and Accounting Research, 2023)
This research aims to find out the influence jointly or partially between remuneration, work environment and competence to the job satisfaction of the Workers at the Sekolah Menengah Kejuruan Swasta Siti Banun. This research uses descriptive qualitative method using primary and secondary data. The population is the workers of the company. Fifty five become the sample of this research. Data analysis technique used is linear regression which shows that from the three independent variables applied to the regression model (remuneration, work environment and competence). Remuneration is significant for 0,003 which can be concluded that remuneration affects job satisfaction (hypothesis 1 accepted). Work environment has significant value 0,001 which can be concluded that quality of work environment (hypothesis 2 accepted). Competence variable has significant value 0,001 which means that competence influences job satisfaction (hypothesis 3 accepted). Research results show that remuneration, work environment and competence all positively influence the job satisfaction of the workers. It can be proven using the result of regression statistic test with probability value 0,000 obtained which is lower than α (α=0,05). So, it can be said that remuneration, work environment and competence influence positively the job satisfaction of the workers. Thus, hypothesis 4 accepted